Two new species of sarcophaga s. lat. from thailand With a key to species (Diptera: Sarcophagidae) - Tarinee Chaiwong (2018)
During a distribution survey of flies of medical importance around northern Thailand, we discovered two new species of flesh fly Sarcophaga (s. lat.) (Diptera: Sarcophagidae) that also are new to science. The species are Sarcophaga nanensis sp. nov. and Sarcophaga kiyokoae sp. nov. Adults of the former species was recovered from Pua River of Nan province (19° 12′29″ N, 100° 56′ 36″ E) 442 m in northern Thailand, whereas the latter species was collected around Kuang River (19° 0′3″ N, 99° 17′6″ E) 551 m of the lowland forests of Chiang Mai province, northern Thailand. Although these two sarcophagid flies showed similarity in their male terminalia in having large aedeagi and rounded juxta, illustrations of the sternite 5, cercus, surstylus, and anterolateral margin of the aedeagus allow differentiation between them. A key is provided to the adult males of the flesh flies of medical importance in Thailand. © 2009 Entomological Society of America.